Growth analysis of green-leaf lettuce under different sources and doses of organic and mineral fertilization (2019)
The objective of this study was to evaluate the influence of different sources and doses of organic and mineral fertilization on the production of green-leaf lettuce. The experiment design used randomized blocks in a factorial scheme (6×3), with six doses of fertilizers (1 = 0; 2 = 25; 3 = 50; 4 = 100; 5 = 150, and 6 = 200% of the recommended fertilization for green-leaf lettuce crop) and three sources of fertilizers [cattle manure (CaM) and chicken manure (ChM), decomposed, on a wet basis and applied 100% at planting at the doses: CaM – 0, 12.5, 25, 50, 75, 100 Mg ha-1; ChM – 0, 5, 10, 20, 30, 40 Mg ha-1; mineral fertilization (MF) varying the N levels: 0, 37.5, 75, 150, 225, 300 kg ha-1 plus 400 kg ha-1 of P2O5 and 60 kg ha-1 of K2O]. The fertilization with CaM and ChM was more efficient than the MF at increasing the production of green-leaf lettuce, mainly because of  the higher residual effects of P in the Oxisol. The ChM provided a higher soil pH, P and K, while the CaM provided a higher soil Mg, organic carbon and organic matter. The dose with 144% of organic fertilization exclusively on a wet basis corresponding to 72 Mg ha-1 of CaM and 29 Mg ha-1 of ChM resulted in the highest green-leaf lettuce yield.